Prevalence and factors associated with vitamin A deficiency in children and adolescents - Rita de Cássia Ribeiro‐Silva; Itaciara L. Nunes; Ana Marlúcia Oliveira Assis (Brazilian Society of Pediatrics, 2014)
Objective: To identify the prevalence and factors associated with vitamin A deficiency (VAD) in children and adolescents. Methods: This was a cross‐sectional study involving 546 schoolchildren, aged between 7 and 14 years, of both genders, enrolled in public elementary schools. Blood was collected for measurement of serum retinol. The retinol concentration in the samples was determined by high performance liquid chromatography (HPLC). Data were collected on anthropometrics, dietary, demographic, and socioeconomic factors. Polytomous logistic regression was used to evaluate the associations of interest. Results: Approximately 27.5% of the students had retinol values < 30 μg/dL. The multivariate analysis showed, after the appropriate adjustments, a positive and statistically significant association of moderate/severe VAD (OR = 2.19; 95% CI 1.17 to 4.10) and marginal VAD (OR = 2.34; 95% CI 1.47 to 3.73) with age < 10 years. There was also association of VAD moderate/severe (OR = 2.01; 95% CI 1.01 to 5.05) and borderline VAD (OR = 2.14; 95% CI: 1.08 to 4.21) with the anthropometric status of underweight. Lower intake of retinol was detected among those with severe VAD. Conclusion: VAD is a health concern among children and adolescents. Lower weight and younger schoolchildren had greater vulnerability to VAD.